Industrial relations in Ghana : the law and practice - Obeng-Fosu, Patrick (Accra : Ghana Universities Press, 1991)
Reviews trends from the colonial period to the presents. Lists members of the Trade Union Congress and labour administration officials, gives model trade union constitutions and rules for a standing joint negotiating committee, and lists African countries that have ratified ILO conventions.
Includes bibliographical references (pages 147-148) and index.
Keywords: Labor laws and legislation -- Ghana; Industrial relations -- Ghana; history; employers organization; strike; labour dispute; ILO mentioned; statistical table; Relations industrielles -- Ghana; Ghana; bibliography